The Effectiveness of Pre-test and Post-test Using Kahoot in Increasing Students’ Attention - Lukman Samboteng; Bernadetha Nadeak; Girang Razati; Ali Zaenal Abidin; Reza Saeful Rachman (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to determine the effectiveness of the Kahoot application as an evaluation tool for students in terms of student attention. This type of research is quantitative, with a one-shot case study design. The population in this study were all eighth-grade junior high school students, the sampling in this study was through purposive sampling, namely class 8.5. The research instrument consisted of an attention questionnaire through Google Forms and observations. The results of the study found that Kahoot was used in the pre-test and post-test to make students' attention more effective. The average Kahoot in learning is 82.6% or very effective, the average pre-test using Kahoot is 80.07% or very effective, and the post-test average using Kahoot is 82.3% or very effective. Thus, Kahoot is very effective for pre-test and post-test.